PROFESSIONAL TRAINING AND EDUCATION AS THE FOUNDATIONS OF SOCIAL CAPITAL BUILDING - TUȘA, Enache; DOGA, Mirela Mihaela (International Journal of Legal and Social Order, 2022)
Education is a public and common good under the care of states and it is often seen as a societal endeavor that involves an inclusive process of policy formulation and implementation. Social actors and civil society, teachers and educators, the private sector, communities, families, youth and children have important roles in accomplishing the right to a quality education. The role of states is essential in establishing and adjusting the standards and norms designed to achieve gender equality. This rights-based approach ensures not only that girls and boys, women and men have access to and promote learning cycles, but that they are equally treated in and through education. These three fundamental principles summarize not only the normative acts of the UN/UNESCO regarding education for sustainable development and for all, but also those related to human rights, generally contained in regulations. The principles transposed in the documents demonstrate that the regulation and the preocupations in applying the established norms are the attribute of the state, the only one that has the power to generate normative acts, enact and apply, but also to ensure the consolidation of the social capital of man and citizen.